2017
DOI: 10.1007/s10517-017-3968-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of σ1-Receptors on the Cell Model of Huntington’s Disease

Abstract: Huntington's disease is a hereditary neurodegenerative disease that primarily affects striatal neurons. Recent studies demonstrated abnormalities in calcium regulation in striatal neurons in Huntington's disease, which leads to elimination of synaptic connections between cortical and striatal neurons. In the present study, we focused on the neuroprotective properties of σ1-receptor, because one of its main functions is associated with modulation of calcium homeostasis in cells. The application of selective σ1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…It has also been suggested that flux through the glycolytic enzyme GAPDH may be relevant ( 74 ), although the results presented here suggest that the major impairment by mutant HTT occurs after that step in glycolysis. Recent studies have also suggested a possible role of the connection between mitochondria and the endoplasmic reticulum, perhaps via sigma-1 receptors ( 75 , 76 ), agonists of which have been shown to be protective in HD models ( 77 , 78 ). Pyruvate can rescue impaired ATP production caused by sigma-1 mutations ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that flux through the glycolytic enzyme GAPDH may be relevant ( 74 ), although the results presented here suggest that the major impairment by mutant HTT occurs after that step in glycolysis. Recent studies have also suggested a possible role of the connection between mitochondria and the endoplasmic reticulum, perhaps via sigma-1 receptors ( 75 , 76 ), agonists of which have been shown to be protective in HD models ( 77 , 78 ). Pyruvate can rescue impaired ATP production caused by sigma-1 mutations ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many S1R agonists are anti-amnestic, synaptogenetic, and neuroprotective in conditions of neuronal stress (Antonini et al, 2009; Hindmarch and Hashimoto, 2010; Ruscher et al, 2011; Bolshakova et al, 2016). They also mitigate disease and symptoms in experimental models of ALS (Mancuso et al, 2012; Ono et al, 2014; Peviani et al, 2014; Ionescu et al, 2019), Alzheimer’s disease (AD) (Meunier and Hayashi, 2010; Fisher et al, 2016; Maurice and Goguadze, 2017; Hall et al, 2018; Goguadze et al, 2019; Ryskamp et al, 2019), Parkinson’s disease (PD) (Francardo et al, 2014; Francardo et al, 2019) Huntington’s disease (HD) (Squitieri et al, 2015; Geva et al, 2016; Bol’shakova et al, 2017; Garcia-Miralles et al, 2017; Ryskamp et al, 2017; Kusko et al, 2018) stroke (Allahtavakoli and Jarrott, 2011; Ruscher et al, 2011, 2012; Sato et al, 2014; Urfer et al, 2014) and traumatic brain injury (Dong et al, 2016). By contrast, S1R deficiency exacerbates progression of neurological disorders (Mavlyutov et al, 2011, 2013; Ha et al, 2012; Francardo et al, 2014; Miki et al, 2015; Maurice et al, 2018) as well as symptoms commonly associated with neurodegenerative diseases.…”
Section: S1r As a Target For Treating Neurodegenerative Diseasesmentioning
confidence: 99%
“…S1R agonists are procognitive, synaptogenetic and neuroprotective in conditions of neuronal stress (Antonini et al, 2009;Bolshakova et al, 2016;Hindmarch and Hashimoto, 2010;Ruscher et al, 2011) and as a result they are beneficial in experimental models of Huntington's disease (HD) (Bol'shakova et al, 2017;Ryskamp et al, 2017;Squitieri et al, 2015) (Garcia-Miralles et al, 2017Geva et al, 2016;Kusko et al, 2018), Parkinson's disease (Francardo et al, 2014) and AD (Fisher et al, 2016;Hall et al, 2017;Maurice and Goguadze, 2017;Meunier et al, 2006). For example, we discovered that the mixed muscarinic/S1R agonist AF710B prevents the loss of mushroom spines in hippocampal cultures prepared from APP-KI or PS1-KI mice (Fisher et al, 2016).…”
Section: S1r As a Target For Pridopidine In Admentioning
confidence: 99%